Descriptive model of sustainable acting for social innovation development - Costa, Priscila Rezende da; Itelvino, Lucimar da Silva; Monken, Sonia Francisca (Revista de Administração da UFSM, 2021)
Purpose: The concept of social innovation as open, collaborative and social transformation process opens room to reinforce the need of legitimizing social impact businesses and of expanding partnerships for social change, as well as the urgency of establishing professional and more sustainable social innovation environments. Accordingly, we tried to answer the following research question: How can social business performance boost the development of social innovations? Design/methodology/approach: Therefore, we adopted the inductive approach of qualitative paradigm, based on the Grounded Theory, to investigate 24 social businesses. In addition, we adopted the Atlas.ti software for data organization and recovery. Aggregate results allowed us to propose a descriptive model of sustainable performance for the development of social innovations in social business, based on the following propositions: sustainable performance in processes and social innovation, the prevalence of a cooperative environment to solve social issues, professional governance as causal factor to social innovation development, the development of actions focused on public interests as influencing conditions for social innovation development, technical and scientific evaluation of social impacts as strategy to measure the outcomes of developed innovations and the expansion of social impacts as the consequence of the self-negotiation of social affairs. Originality/value: A descriptive model of sustainable acting was proposed for the development of social innovations in social businesses.